A Flexible Supply Chain Management Game. (August 2019) - Shovityakool, Patra; Jittam, Piyachat; Sriwattanarothai, Namkang; Laosinchai, Parames
Background. Educational games are widely used in business classes in general, andsupply chain management (SCM) classes in particular. These games are designed to familiarize students with the real business world. Most SCM games are ready-made, with pre-set learning objectives focusing on a certain module in a supply chain. Intervention. This article presents the new spreadsheet-basedFlexible Supply Chain Management Game (FSCMG) and the findings of itspilot study . FSCMG's features aretransparent to instructors and students alike. It iseasily modifiable to suit an instructor's learning objectives. Method. Six groups of undergraduate students took turns playing three modules, namely a wholesaler, manufacturer, and supplier. There were two groups per module to representtwo supply chains . The students' spreadsheets are analyzed and presented. Results. Students' spreadsheets revealed that they were able to employ SCM conceptual understanding in FSCMG, particularly pricing strategy, inventory management, forecasting, and the relationships within a supply chain. Conclusion. FSCGM helped the students apply their in-class knowledge in a real-world situation and be well prepared for their future careers where an extensive understanding is required.